REPRESENTASI PEREMPUAN TANGGUH TOKOH SRI NINGSIH DALAM NOVEL TENTANG KAMU KARYA TERE LIYE - Raden Rara Diwara Marindrasputri Kusumo Wibowo; Budi Waluyo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the representation of a resilient woman, Sri Ningsih, in Tere Liye's novel "About You," through a cultural feminist perspective. This research is motivated by the limited number of studies that discuss female resilience as a form of inner strength and feminine values ​​in literary works. The study employed a descriptive qualitative approach, with Tere Liye's novel "About You" as its data source. The data consisted of narrative excerpts and dialogues that demonstrate the representation of a resilient woman. Data collection was conducted through reading and note-taking techniques, while data analysis employed content analysis, with the stages of data reduction, data presentation, and conclusion drawing. The results show that the representation of a resilient woman, Sri Ningsih, is manifested through resilience in the face of life's hardships, hard work and independence, and concern for others. This resilience is evident through patience, steadfastness, hard work, and empathy. Based on a cultural feminist perspective, feminine values ​​are a source of strength for women in facing various life challenges. Thus, the novel "About You" presents a representation of a resilient woman who maintains her humanity in difficult situations.